When Women Wrote the Constitution. The Second Paragraph of the Art. 29 Between the Principle of Equality and the Indissolubility of Marriage (Italian Review of Legal History, 2024)
In 1946, Italian women voted for the first time and participated in electing the members of the Constituent Assembly. All the 21 elected women made a decisive contribution to drafting the Italian Fundamental Charter. This essay investigates the birth of the second paragraph of Article 29, which ruled the principle of equality between spouses, putting an end to centuries of asymmetries. Nilde Iotti, Angela Guidi Cingolani, Maria Maddalena Rossi, and Nadia Gallico Spano were among the protagonists who faced both doubts and the defence of the status quo, i.e. a hierarchically organised family with a husband at the head. Article 29 was not effectively implemented until the 1975 reform of family law, but a significant fragment of Italian history was written thanks to those women, who fought together for the improvement of women’s conditions despite their political and ideological differences.
Keywords: Constitution; Art. 29; Family; Constituent Mothers